Исследования химико-физических свойств воды, обработанной контактным способом нагрева - Никольский, Валерий Евгениевич; Лободенко, Антонина Викторовна; Решетняк, Ирина Леонидовна (НТУ "ХПИ", 2016)
Выполнены исследования влияния на качество воды контактного тепломассообмена с продуктами сгорания при барботаже в условиях работы аппарата погружного горения (АПГ). Топливо – природный газ. Основные показатели качества воды сопоставленные с допустимыми значениями в соответствии стандартам и нормам. Полученные данные подтвердили возможность, целесообразность и безопасность использования контактного обогрева воды. При работе АПГ обеспечивается высокая равномерность температурного поля по поверхности и объёму ванны, заполненной жидкостью.

The influence of contact heat and mass-transfer processes of combustion products at bubbling at immersed combustion apparatuses action was studied. The gaseous fuel was used. The main points of water quality were compared at different temperatures with standard points, such as colour, turbidity, hardness, oxidability, alcalinity. The mentioned standards were not changed. Concentration of nitrates and nitrites were lower then the limit concentration by 10 and 3 times respectively, sulfates – by 2 times and chlorides – by 12 times. The influence of contact time of combustion products with liquid phase upon the 9 main water quality standards was also studied. The obtained data show the possibility and safety of contact water heating. The steady temperature field through the surface and through the volume of the bath with liquid was observed. And there was no additional metal tube corrosion in the heating systems.
The study physical-chemical properties of water treated by contact heating method
Keywords: аппарат погружного горения; контактный тепломассообмен; концентрация; immersed combustion apparatuses; concentration